(untitled) (Academia Science Repository, 2023)
The article deals with the theoretical basis for the formation of financial and credit policy of commercial banks in Uzbekistan. It shows the concept of credit policy of commercial banks, the processes of its formation, the goals and elements of credit policy, as well as shows a number of factors that affect the choice of credit policy of the Bank. It also describes the process of forming a credit policy, the main problems of the Bank’s financial and credit policy, and recommendations for improving its condition.